A tumor-microenvironment-responsive nanomaterial for cancer chemo-photothermal therapy. Issue 37 (9th June 2020) - Wang, Kaiyu; Cai, Zhiyuan; Fan, Rong; Yang, Qian; Zhu, Tao; Jiang, Zhongying; Ma, Yuqiang
Abstract : Endogenous hydrogen peroxide was utilized to control the release of agents for better tumor therapeutic effect and safety. Abstract : Taxol (TAX) is a typical anticancer drug that is widely used in clinical treatment of cancer, while gold nanorods (AuNRs) are a kind of well-known material applied for photothermal therapy (PTT). The therapeutic outcome of TAX in chemotherapy is however limited by drug resistance, while AuNRs often show poor accuracy in PTT. To optimize the functions of TAX and AuNRs, we developed a hydrogen peroxide (H2 O2 )-triggered nanomaterial (LV–TAX/Au@Ag) for combined chemo-photothermal therapy. In normal tissues, TAX is protected in the lipid bilayer and isolated from the surrounding normal cells, while AuNRs are coated with silver shells and show low photothermal capacity. However, after reaching the tumor tissues, the silver shells can be etched by endogenous H2 O2 in the tumor microenvironment, and the photothermal properties of AuNRs are then recovered. Meanwhile, the generated oxygen destabilizes the LV, which makes the 100 nm sized nanosystems disassemble into the smaller sized TAX and AuNRs, leading to the deep penetration and direct interaction with tumor tissues. The related in vitro experiments proved the validity of this "turn off/on" effect. Extensive necrosis and apoptosis were observed in the tumor tissues and the proliferation of solid tumor was greatly suppressed due to this combined chemo-photothermal therapy. In addition, no significant damage was found in normal tissues after the treatment of LV–TAX/Au@Ag. Therefore, the strategy to achieve environmental response by modifying the photothermal agents enhanced the efficiency and safety of nanomedicine, which may help improve cancer treatment.